Analisis Faktor-Faktor Penentu Pembiayaan Perbankan Syariah pada Sektor Pengangkutan dan Komunikasi di Indonesia - Yozar Putra Jaya; Wiwiek Rindayati; Khalifah Muhammad Ali (Department of Islamic Economics, IPB University, 2015)
The Transportation and communications sector acts as liaison between economy of islands in Indonesia, it’s required helping through the distribution of Islamic Banking funding. This study aims to analyze the influence, shock response, and variety contribute of some factors as banking performance, macroeconomic condition, rate of return, and monetary instruments towards trasportation, warehousing, and communication (TWC) financing in Islamic banking. This study uses Vector Error Correction Model. The results of this study, first, in the short term DPK variabel is affected significantly towards ratio of financing TWC sectors. In the long term NPF, INF, ERP, PUAS, SBK variabels are giving significantly negative effect towards ratio of financing TWC sectors, whereas IPI and BSBIS variabels are giving significantly positif effect. Second, the ratio of TWCsectors responds negatively to the shock of NPF, PUAS, ERP, and INF variabels, whereas the shock of DPK, BSBIS, and SBK variabels is responded positively by the ratio of TWC sectors. Third, BSBIS variable gives the largest contribution to the diversity of financial ratios TWC, then proceed ERP, NPF, and IPI